The effect of health education to parent’s behaviours on managing fever in children - Herman, Hermalinda; Nurshal, Deswita (International Journal of Research in Medical Sciences, 2017)
Background: Fever is one of the common signs that indicate the changes in the body. Generally, parents will do some aggressive actions in dealing with febrile children at home, especially in the use of antipyretic drugs that are not required by the body. The aim of this study is to describe the effect of health education on knowledge, attitude, and action of parents in managing fever of children in Pariaman’s General Hospital. The results of this research can be considered as one of the interventions in the treatment of children in hospital. Methods: The study design is a quasi-experimental with nonequivalent control group approach. Samples are parents who have children with fever sign that were treated in Pariaman’s General Hospital, West Sumatera, Indonesia. Samples were taken by a purposive sampling technique that is in accordance with the criteria set by the researchers. The samples were divided into two groups: the intervention and control groups. Health education about fever was given into intervention groups. In the control groups they received standard care from hospital. The data was collected by questionnaire, that consist of questions about knowledge, attitude an action of parent toward fever in their children. The data statistical was analyzed with independent t test. Results: There are significant differences on knowledge score (p value: 0.009), attitude (p value: 0:03) and action (p value: 0002) of parents between the intervention group and the control group. Conclusions: Therefore, it is expected that health workers and nurses can provide education / health education to parents about fever management in children.